2007
DOI: 10.1183/09031936.00040806
|View full text |Cite
|
Sign up to set email alerts
|

Moisture damage and childhood asthma: a population-based incident case-control study

Abstract: Most previous studies on the association between moisture damage and asthma have been cross-sectional and relied on self-reported exposure and health. The present authors studied the association by carrying out careful home inspections among new, clinically determined cases of asthma and controls.New cases of asthma aged 12-84 months (n5121) were recruited prospectively and matched for year of birth, sex and living area with two randomly selected population controls (n5241). Trained engineers visited all homes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
107
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 35 publications
8
107
2
2
Order By: Relevance
“…We also investigated the exposure of visible mould at home and the risk of respiratory disorders. There are a number of studies considering visible mould as a risk factor for respiratory diseases and symptoms among children [1,2,[4][5][6]. We found no association between visible mould and respiratory disorders within the German and Dutch populations.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…We also investigated the exposure of visible mould at home and the risk of respiratory disorders. There are a number of studies considering visible mould as a risk factor for respiratory diseases and symptoms among children [1,2,[4][5][6]. We found no association between visible mould and respiratory disorders within the German and Dutch populations.…”
Section: Discussioncontrasting
confidence: 43%
“…Some studies have shown that visible mould in homes increases the risk of physician-diagnosed asthma and wheezing in children [1][2][3][4][5][6]. A birth cohort study in the USA concluded that 1-yr-old children of asthmatic and allergic mothers who were exposed to high levels of Penicillium, a common genus of mould, were at significantly higher risk for wheeze and persistent cough [7].…”
mentioning
confidence: 99%
“…DIJKSTRA [29] DALES [16] DALES [32] PONSONBY [18] ZHENG [27] CHEN [25] FREEMAN [20] FREEMAN substudy [20] SPENGLER [19] PEKKANEN [33] DONG [17] DONG [22] ANTOVA [15] WARMAN [24] Summary (OR FAGBULE [34] VERHOEFF [31] LI [26] LI [35] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] BRUNEKREEF [21] STRACHAN [37] STRACHAN [38] DIJKSTRA [29] DALES [16] SPENGLER [19] EMENIUS [36] ALPER [39] DONG [17] DONG [22] ANTOVA [15] ROSENBAUM [43] IOSSIFOVA [8] KARVONEN [42] Summary (OR LI [26] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] CHEN [25] BIAGINI [45] IBARGOYEN-ROTETA [44] KOSKINEN substudy [47] KOSKINEN [47] LI [26] LI [35] BRUNEKREEF [21] DONG …”
Section: Discussionmentioning
confidence: 99%
“…One study from China with 1,209 subjects [27], and two studies from Europe [31,33] reported an increased risk of physician-diagnosed asthma with exposure to visible mould, in children up to school age. This association could not be confirmed by LI and HSU [35] in a small population of 46 Taiwanese school children.…”
Section: Wheezementioning
confidence: 99%
“…Without changes to ventilation, houses become tighter with increased insulation which results in deteriorating indoor air quality due to increased humidity but also in greater thermal comfort and less infiltration of polluted ambient air in cities. Although indoor air quality can significantly affect health (Pekkanen et al, 2007) it was out of scope to estimate these very complex effects.…”
Section: Discussionmentioning
confidence: 99%